2018
DOI: 10.1021/acs.jpcb.8b03279
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Drug-Induced Changes in Metabolite Populations of Live Bacteria: Real Time Analysis by Raman Spectroscopy

Abstract: Raman difference spectroscopy is shown to provide a wealth of molecular detail on changes within bacterial cells caused by infusion of antibiotics or hydrogen peroxide. Escherichia coli strains paired with chloramphenicol, dihydrofolate reductase propargyl-based inhibitors, meropenem, or hydrogen peroxide provide details of the depletion of protein and nucleic acid populations in real time. Additionally, other reproducible Raman features appear and are attributed to changes in cell metabolite populations. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…), respectively. This is well in agreement with the mechanism of action of ciprofloxacin, which binds to DNA gyrase, producing ciprofloxacin–gyrase DNA ternary complexes. ,,,, These complexes can inhibit DNA replication and RNA transcription, causing massive DNA fragmentation and preventing cell growth, leading to bacterial cell death. Fluoroquinolones increase reactive oxygen spp.…”
Section: Discussionsupporting
confidence: 76%
“…), respectively. This is well in agreement with the mechanism of action of ciprofloxacin, which binds to DNA gyrase, producing ciprofloxacin–gyrase DNA ternary complexes. ,,,, These complexes can inhibit DNA replication and RNA transcription, causing massive DNA fragmentation and preventing cell growth, leading to bacterial cell death. Fluoroquinolones increase reactive oxygen spp.…”
Section: Discussionsupporting
confidence: 76%
“…Changes in cellular composition can be monitored using changes in Raman band profiles, which can be associated with the morphological changes of microbial cells, providing an image of the antimicrobial effect [24]. Recent reports have shown that Raman difference spectroscopy is able to provide molecular details on changes within E. coli cells caused by antibiotics, hydrogen peroxide [20,25] or graphene oxide [19]. In this work, the interaction of PchNPs with E. coli caused a decrease in the intensity of most Raman bands, while other remain the same ( Table 1).…”
Section: Antimicrobial Properties Of Pchnps Using Confocal Raman Micrmentioning
confidence: 99%
“…Raman spectroscopy and its derivatives, coupled with multivariate analysis, have been applied mainly to cancer diagnosis [ 12 – 19 ] on a range of sample formats, including fixed cells and tissues, as well as non-invasive biofluid measurements [ 20 ] has been used also in diagnosis and study of other diseases due to viral or bacterial infections [ 21 ], even to study biofluid profile after COVID-19 infection [ 22 ], until it has been used in neurodegenerative disease diagnosis [ 23 ]. Raman spectroscopy has been also applied to study stem cells [ 24 ], cell lines in vitro [ 25 ] and metabolomics [ 26 ].…”
Section: Introductionmentioning
confidence: 99%